Ditribuição de terras raras e outros elementos incompatíveis no Maciço de Monchique; nota preliminar - Simão, J. (2010)
When approaching a geochemical project a few problems of methodology have to be considered, among them the exploration grid that as to obey to representativity/rentability criteria. This preliminary study permitted to save near 27% on the sampling comparing with the net initially envisaged. Some criteria considered in the elaboration of the grade variation maps and the distribution of two elements in the area already sampled are also presented.